Modern aspects of superconductivity : theory of superconductivity - Kruchinin, Sergei (World Scientific, 2011)
Superconductivity remains one of the most interesting research areas in physics and stood as a major scientific mystery for a large part of this century. This book, written for graduate students and researchers in the field of superconductivity, discusses important aspects of the experiment and theory surrounding superconductivity. New experimental investigations of magnetic and thermodynamic superconducting properties of mesoscopic samples are explored with the help of recent developments in nanotechnologies and measurement techniques, and the results are predicted based upon theoretical models in nanoscale superconducting systems. Topics of special interest include high-Tc superconductivity, two-gap superconductivity in magnesium diborades, room-temperature superconductivity, mechanism of superconductivity and mesoscopic superconductivity. Particular attention is given to understanding the symmetry and pairing in superconductors. The theory of the Josephson effect is presented and its application in quantum computing are analyzed.